2018
DOI: 10.12688/f1000research.12886.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding and managing retinal vein occlusions

Abstract: Retinal vein occlusions are the second most common form of retinal vascular disease. Previously, laser treatment for branch retinal vein occlusion and intravitreal triamcinolone acetonide for central retinal vein occlusion were the standard of care. Recent studies have demonstrated that anti-vascular endothelial growth factor (anti-VEGF) agents have a superior safety and efficacy profile for the treatment of both branch and central retinal vein occlusions. The use of wide-field fluorescein angiography has also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…There are new VEGF inhibitors, biosimilars, and drug delivery systems for treating retinal vascular diseases in the pipeline. Conbercept is a new approved anti-VEGF drug for treating nAMD which is currently available only in China [52,53]. Conbercept can inhibit all VEGF isoforms and placenta growth factor and has the longer half-life (7 days) than the other anti-VEGF drugs which allows as-needed dosing regimen [54].…”
Section: Five-year Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are new VEGF inhibitors, biosimilars, and drug delivery systems for treating retinal vascular diseases in the pipeline. Conbercept is a new approved anti-VEGF drug for treating nAMD which is currently available only in China [52,53]. Conbercept can inhibit all VEGF isoforms and placenta growth factor and has the longer half-life (7 days) than the other anti-VEGF drugs which allows as-needed dosing regimen [54].…”
Section: Five-year Viewmentioning
confidence: 99%
“…Brolucizumab is a humanized single-chain antibody fragment with high binding affinity. The phase 3 trials comparing brolucizumab to aflibercept in nAMD patients demonstrated non-inferiority in mean BCVA gain and safety profile between both drugs, and efficacy of brolucizumab could be maintained with 12-week dosing intervals after the loading phase through week 48 [52,53]. The biosimilar versions of ranibizumab (PF582) and bevacizumab (BCD021) have undergone clinical studies [54].…”
Section: Five-year Viewmentioning
confidence: 99%
“…It induces circulatory slow-down and upstream blood stasis appearing in the form of retinal hemorrhages [ 3 ]. CRVOs were classically separated into two clinical forms: ischemic CRVO (also possibly associated with cotton-wool spots) and nonischemic CRVO [ 4 ], the former being regarded as the more severe due to VEGF-mediated neovascular complications [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, BRVO is 4 to 6 times more prevalent than CRVO (4) since the worldwide prevalence of RVO is 0.052% for any RVO, 0.042% for BRVO, and 0.008% for CRVO (5). CRVO in young adults is uncommon; only 10% to 15% of patients with CRVO are under 40 years of age (6). Furthermore, the occlusion patterns of BRVO and CRVO are entirely dissimilar.…”
Section: Introductionmentioning
confidence: 99%
“…Among the elements of Virchow's triad, the contribution of thrombogenesis or hypercoagulability of blood has not been as well investigated as the other 2 two factors. Therefore, the contribution of various hematological abnormalities to the etiology, pathogenicity, and treatment of CRVO remains unclear and there are contrasting clinical results (6)(7)(8)10).…”
Section: Introductionmentioning
confidence: 99%